Rights and Comfort Masyarakat Non Muslim atas Perwujudan Pariwisata Halal: Kritik dan Gagasan - Damanik, Deniansyah; Monica, Eka Syafrina (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2024)
Halal tourism in which there are halal products and even the halal industry brings understanding to non-Muslim communities in tourist areas where the majority are non-Muslims as if there was eviction or even coercion on non-Muslim communities and even eliminating rights, losses and even comfort. non-Muslim communities in areas where halal tourism will be built. Therefore, it is necessary to explain about the rights of non-Muslim communities and also their comfort regarding the existence of halal tourism. In this study the author uses literature research to assist the author in completing this paper well. Therefore, regarding the understanding of non-Muslim communities about halal tourism and lest their rights and comfort be disturbed, basically they still have the right to do activities, the right and comfort to get protection, the right to the ability to access the same as well as the right to gain insight into other things. Islam and halal tourism